Post-harvest losses - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
Reducing post-harvest losses in perishable crops (fruits, vegetables, roots, tubers, nuts, spices and beverage crops) can be seen as a priority in the campaign to maximize the Third World's potential for self sufficiency. PIPIC (Postharvest...